Influencer marketing - Aguiar, Tatiana Domingues, ....-; van Reijmersdal, Eva, ....- (Amsterdam : SWOCC, 2018)
Social influencers have become extremely popular. Influencer's success is illustrated by overwhelming numbers of followers, likes, tweets and retweets. As a result, more and more brands are interested in influencer marketing. However, it is often hard to decide whether influencer marketing is a valuable tool and whether it benefits your objectives. This publication provices insights into the key characteristics of influencer marketing and helps you decide wheter influencer marketing fits you business strategy.
Keywords: marketing